Assessment of the readiness of health facilities in urban areas to deliver geriatric-friendly care services: a cross-sectional study in Kampala City, Uganda - Ainembabazi, Peruth; Gwokyalya, Anna Maria; Twinamasiko, Nelson; Kihumuro, Raymond Bernard; Kintu, Timothy Mwanje; Bongomin, Felix (BMC geriatrics, 2024)
Background: With the global rise in the elderly population, ensuring geriatric-friendly healthcare services is paramount. This study aimed to assess the current readiness of health facilities in Kampala City, Uganda, to provide geriatric-friendly care services. Methods: We conducted a cross-sectional study in 35 health facilities (HF) including Private for-profit (PFP), Private not-for-profit, and public (government-run) facilities at different levels i.e., Health Centre III, Health Centre IV, and Hospitals, within Kampala City, Uganda. Data was collected using a self-administered health facility assessment tool. Facilities scoring 80–100 were classified as fully ready to offer geriatric-friendly care, 51–79 indicated moderate readiness, and 0–50 indicated low readiness. Results: The overall readiness index (RI) across all facilities was low, 44.09 (SD ± 14.18). The National Referral Hospital (NRH), PFPs, and HFs in Kampala Central had the highest RI of 55.34. 47.63 and 51.09 respectively. The low readiness of HF to provide geriatric-friendly care was due to the low scores in leadership and governance (13.49), financing (19.29), human resource (42.66), and Health Management Information System (47.99) WHO building blocks. HCIVs had a higher readiness index than the other HF levels (Coefficient: 17.40, 95% CI: 4.16 to 30.64, p = 0.012). HFs in Kawempe had a significantly lower RI than those in Makindye and Kampala Central (Coefficient: -13.80, 95% CI: -24.48 to -3.11, p = 0.013). Conclusion: The findings of our study indicate that public and private health facilities in Kampala City are not ready enough to provide geriatric-friendly care services.
Keywords: Geriatric-friendly care services; Health facility readiness; Urban areas; Geriatric care in Uganda